DUKUNGAN TEKNOLOGI PENGEMBANGAN KEDELAI DI SUMATERA BARAT (Technological Support of Development Soybean in West Sumatra) - Atman Atman (Jurnal Penelitian Pertanian Terapan, 2011)
Soybean production in the province West Sumatra from 1996 until 2009 does not seem stable from year to year and even a drastic decrease, reaching 76%. Soybean productivity is still low (range from 1.10 to 1.69 t/ha) compared to its potential and abroad that can reach 2.5 to 3 t/ha with a harvest area fluctuates very significantly. Meanwhile, the need for raw materials by the company's soybean processing tahu/tempe enough large, which is 241.05 tons per month, or 2,892.6 tons per year. This article contains about the problems of soybean and technological support for the development of soybean (low land and dry land) in West Sumatra. The methodology of writing a book study (literature) on soybean commodity that comes from books, proceedings, journals, papers and others. The result, soybean development strategy in the province of West Sumatra can be directed at three main agro-ecosystem, namely: irrigated land, rainfall land and dry land. However, in the lowland rice (43 817 ha of rainfall rice, 43,094 ha of lowland rice irrigated villages, 48,069 ha of lowland rice simple irrigated, and 67,457 ha of lowland rice irrigated semi-technical) and upland (gardens/ 329 528 ha, field for dry rice cultivation 132,240, and 595,516 ha of plantation) the greatest potential for development of soybean plants. Mechanical cultivation of soybean in lowland and dryland in almost the same. However, in some cases there are differences, especially the use of new varieties, land preparation, and delivery of lime /organic materials.Key words: soybean, technology, low land, dry land, West Sumatra.